Kearifan Lokal dalam Membangun Kerukunan Islam dan Hindu di Desa Adat Kuta Badung (Local Wisdom in Building Harmony of Islam and Hindu in The Traditional Village of Kuta Badung) - Yantos Yantos; Putriana Putriana (Jurnal Dakwah Risalah, 2020)
This study aims to determine the local wisdom of the people of Desa Adat Kuta, Badung Regency, Bali Province, in building harmony between Muslims and Hindus. This study uses social integration theory as a basis for seeing the assimilation and unification of Muslims and Hindus. This study used a qualitative method with the research subjects of village officials, Muslim and Hindu religious leaders, and community leaders. The results showed that the community's wisdom in the Desa Adat Kuta is a hereditary tradition, in the form of mutual agreement in regulating the relationship between Muslims and Hindus, based on the teachings and principles of their respective religions. The sense of kinship in the Desa Adat Kuta is woven through the Nyama Selam and Nyama Hindu traditions. The harmony of Muslims and Hindus is manifested in the freedom to practice worship, Muslims based on the teachings and principles of Ukhuwah Insaniyah and Hindus based on the teachings and principles of Tri Hita Karana. The existence of equality and tolerance does not lead to conflict, including in establishing places of worship because they are regulated by the government and there is intense communication in the Forum for Religious Harmony.